2005
DOI: 10.1149/1.1859631
|View full text |Cite|
|
Sign up to set email alerts
|

ALD of Hafnium Oxide Thin Films from Tetrakis(ethylmethylamino)hafnium and Ozone

Abstract: Hafnium oxide (HfO 2 ) thin films were deposited from tetrakis͑ethylmethylamino͒hafnium ͑TEMAH͒ and ozone (O 3 ) by atomic layer deposition ͑ALD͒ on 200 mm silicon wafers. The O 3 half-reaction shows good saturation behavior. However, gradual surface saturation is observed for the TEMAH half-reaction. Within wafer non-uniformity of less than 1% and step coverage of about 100% were achieved for trenches with aspect ratio of around 40:1. The film thickness increased linearly as the number of cycles increased. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
141
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 9 publications
10
141
0
Order By: Relevance
“…For HfO x , atomic layer deposition (ALD) is often the tool of choice due to the self-limiting growth regime allowing a uniform, stoichiometric and well controlled layer to be deposited [11][12]. When trying to alter the oxygen concentration however, an increase in oxygen flow rate does not necessarily result in an increase in oxygen due to the selflimiting growth reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For HfO x , atomic layer deposition (ALD) is often the tool of choice due to the self-limiting growth regime allowing a uniform, stoichiometric and well controlled layer to be deposited [11][12]. When trying to alter the oxygen concentration however, an increase in oxygen flow rate does not necessarily result in an increase in oxygen due to the selflimiting growth reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for some materials it has been reported that improved film properties are obtained when using O 3 or O 2 plasma instead of H 2 O. [2][3][4][5][6][7][8] The potentially more favorable process settings ͑e.g., in terms of substrate temperature and purge times͒ as well as the potentially improved material properties obtained for the O 3 and O 2 plasma based ALD processes have also contributed to an increased interest into ALD by other fields of technology than semiconductor industry. Potential application of ALD films in areas such as microsystems, solar cells, flexible electronics, energy storage, and photonics have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…ALD recipes for Al 2 O 3 came from Goldstein, 10 MgO from a custom reaction developed at JPL by the authors, SiO 2 from Dingemans 12 and HfO 2 from Liu. 13 Often growth recipes required modifications to accommodate the equipment used. Modified growth recipes were typically validated using either XPS, TEM, or both.…”
Section: Deposition Techniquesmentioning
confidence: 99%